PENGARUH BALANCE EXERCISE TERHADAP RISIKO JATUH PADA LANSIA DI WILAYAH KAMPUNG TUA DAPUR 12 - UMI ELIAWATI; Rizki Sari Utami Muchtar; Mery Kristian Agustina Hutagalung (LPPM STIKes Mitra Adiguna, 2026)
Until now, fallling incidents remain a dangerous problem, with older adults falling into the high-risk category due to health issues such as balance disorders. Research on the effects of balance exercises on fall risk in the elderly is based on the consideration that interventions are needed to help reduce fall risk in the elderly. The study purpose was to determine the effect of balance exercises on the risk of falling among elderly people in the Kampung Tua Dapur 12 area. Used a pre experimental with a one-group pretest-posttest. The sample used purposive sampling technique consisted of 20 elderly. Data analysis was using a paired t-test that showed that the average fall risk before performing balance exercises was moderate fall risk of 60% and a low fall risk of 40%. After performing, an average low fall risk of 80% and a moderate fall risk of 20%. The effect was a decrease of 9. With a ?-value = 0.000 < ? 0.05, there is a significant difference between the average reduction in the risk of falling before and after balance exercise. For next studies, researchers suggest doing longer investigations and using helpers to assist with checking and treating the elderly, since each person needs to be watched closely, which takes more time and effort. Also advise community groups to start again the exercise program for older adults and recommend balance activities as a type of exercise for the elderly, along with health services, which should also get support from the elderly's family members.